Hubungan Pola Makan, Kebugaran Jasmani Dan Stres Terhadap Kondisi Obesitas Personel POLRI - Putra, Novi Setyawan (Gelanggang Olahraga: Jurnal Pendidikan Jasmani dan Olahraga (JPJO), 2025)
This study aims to determine how big the relationship is: Diet, Physical Fitness, and Stress on the obesity condition of Police personnel. This type of research is correlational. This research was conducted with subjects totaling 584 police personnel. The instruments used in this study are dietary instruments using the Food Frequency Questionnaires for Adults, Physical Fitness Instruments using the Polri Physical Fitness Test, and Stress Instruments using the Polri E-Mental Application. Data analysis techniques in this study using product moment correlation test analysis, multiple correlations using regression line equations, prerequisite tests and hypothesis tests as well as univariate and bivariate analysis. Based on the results of this study showed: there is a relationship between diet and obesity of police personnel with a p-value of 0.631 with a sig. value of 0.000; there is a relationship between physical fitness and obesity of police personnel with a p-value of 0.433 with a sig. value of 0.000; there is a relationship between stress levels and obesity of police personnel with a p-value of 0.429 with a sig. value of 0.000. That there is a fairly strong relationship between diet, physical fitness, and stress on the condition of obesity in Polri personnel, and it can be seen that diet has the most significant influence compared to physical fitness and stress. Keywords: Dietary habit, Physical fitness, Stress, Obesity.